Observational Study of 180° Turning Strategies Using Inertial Measurement Units and Fall Risk in Poststroke Hemiparetic Patients - Barrois, Rémi Pierre-Marie; Ricard, Damien; Oudre, Laurent; Tlili, Leila; Provost, Clément; Vienne, Aliénor; Vidal, Pierre-Paul; Buffat, Stéphane; Yelnik, Alain P. (Frontiers in Neurology, 2017)
Objective - We analyzed spontaneous 180° turning strategies in post-stroke hemiparetic patients by using inertial measurement units (IMUs) and the association of turning strategies with risk of falls. Methods – We included patients with right hemiparesis (RP), left hemiparesis (LP) and healthy controls (HC) from a physical and rehabilitation department in France between July 2015 and October 2015. All subjects were right-handed and right-footed for mobilization tasks. Participants were instructed to turn 180° in a self-selected direction after a 10-m walk while wearing 3 IMUs on their trunk and both feet. We defined 3 turning patterns based on the number of external steps (pattern I= 1; II= 2-4 steps; III ≥5) and 4 turning strategies based on the side chosen to turn (healthy or paretic) and the stance limb used during the first step of the turn (healthy or paretic). Falls in the 6 months after measurement were investigated. Results – We included 17 patients with RP (mean [SD] age 57.5 [9.5] years [range 43 to 73]), 20 with LP (mean age 60.7 [8.8] years [range 43 to 63]) and 15 HC (mean age 56.7 [16.1] years [range 36 to 83]). The LP and RP groups behaved similarly in turning patterns, but 90% of LP patients turned spontaneously to the paretic side versus 59% of RP patients. This difference increased with turning strategies: 85% of LP versus 29% of RP patients used strategy 4 (paretic turn side with paretic limb). Patients using strategy 4 had the highest rate of falls. Conclusion –We propose to consider spontaneous turning strategies as new indicators to evaluate the risk of fall after stroke. IMU could be routinely used to identify this risk and guide balance rehabilitation programs.